2012
DOI: 10.1016/j.ajo.2011.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Vision Health Disparities in the United States by Race/Ethnicity, Education, and Economic Status: Findings From Two Nationally Representative Surveys

Abstract: Purpose To assess vision health disparities in the United States by race/ethnicity, education, and economic status. Design Cross-sectional, nationally representative samples Methods We used national survey data from the National Health and Nutrition Examination Survey (NHANES) and the National Health Interview Survey (NHIS). Main outcome measures included, from NHANES, age-related eye diseases (i.e., age-related macular degeneration [AMD], cataract, diabetic retinopathy [DR], glaucoma) and from NHIS, eye c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
155
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(173 citation statements)
references
References 36 publications
4
155
2
Order By: Relevance
“…Even in the United States, annual use of eye services was significantly associated with levels of educational attainment after adjusting for other factors. [32][33][34] A randomized controlled trial demonstrated that educational interventions can successfully increase the uptake of cataract surgery. 35 Sex differences in the health burden of cataract vision loss were significant for each age group.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the United States, annual use of eye services was significantly associated with levels of educational attainment after adjusting for other factors. [32][33][34] A randomized controlled trial demonstrated that educational interventions can successfully increase the uptake of cataract surgery. 35 Sex differences in the health burden of cataract vision loss were significant for each age group.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the US, African Americans have a high prevalence of type 2 diabetes and seem to be at high risk for microvascular complications, including diabetic retinopathy (DR). 2 Some studies have found that African Americans have a higher risk of developing DR compared with Caucasians after adjusting for clinical risk factors. 37 For example, the prevalence of moderate non-proliferative DR or worse was higher for African American veterans than for Caucasian veterans in the Veterans Affairs Diabetes Trial of type 2 diabetes, and could not be accounted for by traditional risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although education and income traditionally have been considered as ''modifiable'' risk factors, the education-and income-related health disparities remain significant, and persistent in the United States and many other countries. 27 Previous health initiatives have not yielded effective and practical approaches, and, most importantly, evidence of significant outcomes in addressing these disparities.…”
Section: Discussionmentioning
confidence: 99%